Altered Pattern of Macrophage Polarization as a Biomarker for Severity of Childhood Asthma - Kuo CH; Tsai ML; Li CH; Hsiao HP; Chao MC; Lee MS; Lin YC; Hung CH (Dove Medical Press, 2021)
Chang-Hung Kuo,1,2 Mei-Lan Tsai,3 Chung-Hsiang Li,2,4 Hui-Pin Hsiao,4 Mei-Chyn Chao,4 Ming-Sheng Lee,4 Yi-Ching Lin,5- 8 Chih-Hsing Hung3,4,9 1Ta-Kuo Clinic, Kaohsiung, Taiwan; 2Department of Pediatrics, Kaohsiung Municipal Ta-Tung Hospital, Kaohsiung, Taiwan; 3Graduate Institute of Medicine, College of Medicine, Kaohsiung Medical University, Kaohsiung, Taiwan; 4Department of Pediatrics, Kaohsiung Medical University Hospital, Kaohsiung Medical University, Kaohsiung, Taiwan; 5Department of Laboratory Medicine, Kaohsiung Medical University Hospital, Kaohsiung Medical University, Kaohsiung, Taiwan; 6Department of Laboratory Medicine, School of Medicine, College of Medicine, Kaohsiung Medical University, Kaohsiung, Taiwan; 7Ph.D. Program in Toxicology, College of Pharmacy, Kaohsiung Medical University, Kaohsiung, Taiwan; 8Substance and Behavior Addiction Research Center, Kaohsiung Medical University, Kaohsiung, Taiwan; 9Department of Pediatrics, Kaohsiung Municipal Hsiao-Kang Hospital, Kaohsiung, TaiwanCorrespondence: Chih-Hsing HungDepartment of Pediatrics, Kaohsiung Municipal Hsiao-Kang Hospital, No. 482, Shanming Road, Siaogang District, Kaohsiung, 812, TaiwanTel +886-7-3121101-6506Fax +886-7-3213931Email pedhung@gmail.comPurpose: Asthma causes a substantial morbidity and mortality burden in children and the pathogenesis of childhood asthma is not completely understood. Macrophages are heterogeneous with divergent M1/M2 polarization phenotypes in response to various stimulations during the inflammatory process. We aimed to investigate the pattern of macrophage polarization and its association with severity and exacerbation in asthmatic children.Patients and Methods: Normal and asthmatic children aged 4- 18 years were enrolled for 12 months. Children with asthma were further subgrouped according to their severity and the requirement for hospitalization during exacerbations. Clinical data were obtained from medical records. Peripheral blood samples were collected to analyze macrophage polarization, including M1, M2, and subsets, by flow cytometry.Results: Fifty-one asthmatic cases and 27 normal controls were included in this study. The level of PM-2K+CD14+ but not PM-2K+CD14− was decreased in asthmatic children. The levels of M2a (CCR7−CXCR1+), M2b (CCR7−CD86+), and M2c (CCR7−CCR2+) subsets, but not M1 (CCR7+CD86+), were increased in asthmatic children. The levels of M1 were decreased, but the levels of M2c were increased, in children with moderate asthma compared to those with mild asthma. The levels of PM-2K+CD14+ cells and M1 subsets were decreased, but the M2c subset cells were increased in asthmatic children requiring hospitalization during exacerbations.Conclusion: Macrophage polarization may be involved in the pathogenesis of childhood asthma and is a potential biomarker of childhood asthma disease severity.Keywords: M2 macrophage polarization, asthma severity, asthma exacerbation, childhood asthma hospitalization